The Use of Torbangun Leaf Powder (Coleus amboinicus L) in Increasing Prolactin in Breastfeedings Wistar Rats and Bodyweight of the Litters - Stella T Hasianna; July Ivone; Sifa D Shinta; R Zahra Nadhira (Journal of Medicine and Health, 2021)
Research on local herbs that have the effect of increasing breast milk production isneeded to help mothers with insufficient breastmilk. This research was conducted to determinethe effect of torbangun (Coleus amboinicus L) leaf powder in increasing prolactin inbreastfeeding Wistar rats and the bodyweight of the litters. Thirty breastfeeding Wistar rats weredivided into 5 groups with 5 litters each. The treatments given were 108 mg, 216 mg, and 432 mgtorbangun leaf powder (TLP), with domperidone as the positive control, and CMC 10% as thenegative control. The treatment was given 3 times/day for 14 days. Tukey's HSD means testshowed a significant difference in prolactin levels between the negative control (NC), TLP1, andTLP2 groups and the TLP3 and positive control (PC) groups with all of them having p = 0.000.There was no difference in the increase in body weight of litters between treatment groups (p =0.866). In conclusion, torbangun leaves increase the prolactin levels in breastfeeding rats buthave no difference in the increase in body weight of litters between treatment groups. Keywords: torbangun leaves; prolactin; bodyweight; breastfeeding